Investigation of Agricultural Waste as Economical and Effective Bio-Inhibitors for Inhibiting Scaling in Natural Hard Water - Souiad, Faléstine; Bendaoud-Boulahlib, Yasmina; Kerkatou, Wafa; Fernandes, Annabel; Aissa, Chibani; Lopes, Ana (KnE Materials Science, 2022)
In this study, agricultural waste was utilized as new bio-inhibitors to prevent scale formation in hard waters. Aqueous extracts of strawberry and tomato leaves were utilized for reducing the scale deposits formed on metallic surfaces by Bounouara ground hard water, which supplies Constantine city in Algeria. Anti-scaling properties were evaluated by chronoamperometry and impedancemetry techniques. The effect of temperature and concentration on the efficiency of the bio-inhibitors was assessed. The results showed that the anti-scaling effect of strawberry leaf extracts started at the very low concentration of 1 ppm, with 31% efficiency, reaching complete scaling inhibition at 15 ppm (20ºC), whereas the inhibitory effect of tomato leaf extracts was noticed at 2.5 ppm, with 36% efficiency, and total inhibition at 20 ppm (20ºC). The efficiency of strawberry and tomato leaf extracts at 40∘C was also confirmed, although total inhibition was attained at a higher concentration. Keywords: hard water, agricultural waste, strawberry leaves, tomato leaves, bioinhibitors, scaling inhibition